Evidence : text and materials - Uglow, Steve (Sweet & Maxwell, 2006)
Presents a firm grounding in the rules of evidence and the relationship between evidence and procedure, placing this relationship in the broader context of the criminal and civil justice systems. This book also draws together cases, statutes and practical readings on civil and criminal evidence, linked by an interpretative commentary